Exploración de densidad mineral ósea y concentración flúor en orina, en pacientes con fluorosis denta (2022)
Dental fluorosis is an irreversible affectation in the formation of enamel, the result of excessive consumption of fluoride, other effects of chronic exposure to fluoride are skeletal fluorosis and bone fractures.Objective: To identify To carry out an exploration of bone mineral density and fluoride concentrations in urine in children from 7 to 17 years of age with dental fluorosis from the Educational Institution el Juncal of the municipality of Palermo. Materials and methods: A case series study by means of which an analysis of bone mineral density and fluoride concentration in urine was carried out in 17 patients with dental fluorosis. Results: 62% of the children show moderately abnormal concentrations of calcium, with respect to 37.55 with moderately abnormal; for iron 56.25% of the children present normal concentrations, 31.25% moderately abnormal and 12, 5% moderately abnormal; with respect to zinc 37% of the children have normal values and 31, 5% correspond to medium and moderately abnormal values. Conclusions: Half of the children presented a moderately abnormal degree of osteoporosis; on the other hand, none of the children presented severely abnormal values for the variables analyzed.